Plan de negocios para la exportación de velas decorativas a base de cera de soya hacia Estados Unidos (2021)
Currently, candles play a role that, although not very common, is quite important, since it can be said that at least 8 out of 10 people have a candle in their home, either decorative, to illuminate or to strengthen their faith. This class of products is not a traditional export product; therefore it would be a good and innovative source of foreign exchange generation and new sources of employment. The idea of this project is to develop and market candles based entirely on soy wax that not only makes them attractive for their aroma but also for the environmental and health benefits that they entail.